Problem Identification and Conflict Resolution Strategies for Industrial Forest Plantation Licensing in Sekadau Forest Management Unit - Hardiansyah, Gusti; Mardin Rachmad, Harul; Rifanjani, Slamet; Fitriani, Afni (Jurnal Ilmu Kehutanan, 2025)
This research aimed to map tenure conflicts within the Industrial Forest Plantation (HTI) in the Sekadau Forest Management Unit (KPH) and to thoroughly analyze effective strategies for addressing these conflicts. The study employed Rapid Land-Tenure Assessment (RaTA)and Dispute Style Analysis (AGATA) utilizing the Thomas-Kilmann Instrument. The results revealed three distinct disputing styles: Agitation (Karang Betung-Kenyabur, Teluk Kebau-Merabu Jaya), Compromise (Tembesuk-PTWSP), and Collaboration (Nanga Engkulun-PTWSP). Based on these findings, the research recommends tailored strategies for conflict resolution. Neutral mediation strategies are suggested to reduce tensions in agitation-style disputes, while facilitation strategies can help achieve mutually beneficial solutions in compromise-style cases. Trust-building initiatives are advised to enhance collaboration in resolution efforts. Additionally, this research emphasizes the integration of corporate social responsibility (CSR) programs, including forestry partnerships, agroforestry initiatives, non-timber forest product development, and livestock assistance, to provide interim economic benefits. These approaches combine positive law, customary law, and multi-stake holder engagement to effectively resolve conflicts while advancing community welfare and promoting sustainable development.